Optimasi Manajemen Energi pada Oven Hybrid Surya dan Gas Menggunakan Metode Fuzzy Logic - Santy, Farah; Wijanarko, Yudi; Rasyad, Sabilal (Lembaga Pengembangan Kinerja Dosen, 2026)
The increasing global demand for energy and the environmental impact caused by fossil fuel consumption have encouraged the development of renewable energy technologies, particularly solar photovoltaic (PV) systems. However, the intermittent nature of solar energy creates challenges in maintaining a stable energy supply, especially for thermal applications such as ovens. Therefore, this study proposes an energy management system for a hybrid solar–gas oven integrated with a Battery Energy Storage System (BESS) using a Fuzzy Logic Controller (FLC). The proposed system combines solar energy, battery storage, and gas as a backup energy source to ensure a stable thermal energy supply under various operating conditions. The fuzzy logic method is applied to determine the most optimal energy source in real time based on solar radiation intensity, battery state of charge, and thermal load demand. The system is designed to improve energy distribution efficiency, reduce excessive battery usage, and maintain stable oven operation. The results show that the fuzzy logic-based energy management strategy can optimize renewable energy utilization while maintaining system reliability and stability. Therefore, the developed hybrid energy management system has strong potential to reduce dependence on fossil fuels and support sustainable energy applications in thermal processing systems.